Rotavirus vaccination in the US: a systematic review of vaccination coverage and completion - Parinaz K. Ghaswalla; John D'Angelo; Remon Abu-Elyazeed (Taylor & Francis Group, 2021)
A systematic literature review of Medline and Embase databases was conducted to describe rotavirus (RV) vaccine coverage for a complete series, timing of receipt of all doses in the series, and predictors of RV vaccination coverage in the US for two licensed RV vaccines (RV1, RV5). Nine publications were included in the review. RV vaccination coverage rates of under 80% suggest RV vaccines are underutilized relative to the Healthy People 2020 target and other childhood vaccines. About 50-90% of children initiating RV vaccination complete the series and coverage for a complete series is lower for black and Hispanic children (vs. whites), uninsured or Medicaid insured (vs. privately insured), and for foreign-born (vs. US-born) children. Series completion is significantly greater in children receiving DTaP, RV1 (vs. RV5), and for those receiving routine care from a pediatrician. There is a need to design and implement better RV immunization strategies for US children.